BIOPOTENCIALIZACION NUTRICIONAL EN LA PRODUCCION AGRICOLA - Sierra Bernal , Leidy Jhoanna
The purpose of this article is to demonstrate that the development of bio-potentialized products grown in controlled environments, in order to achieve fruits with higher quality of nutrients for the consumers of the sub-urban areas, is an effective method in the improvement of the nutritive quality of agricultural products, decreasing the amount in the diet and increasing the concentrations of nutrients in each fruit, optimizing the nutritional requirements of the human being for the proper functioning of the organism. Through the duality in the application of micro / macro nutrients from the synthesis of active ingredients obtained from plants and the determination of the additive synthesis protocol, the modification in the plant development cycle is obtained, to fix and potentiate the nutritional quality in the fruit The additive synthesis modifies the phases of the development cycle of the plant, allowing in the additional times obtained, to add the nutrients according to the bio-potentialization requirements in the fruit, until achieving the desired characteristics. To ensure the quality of the process and maintain the optimum conditions of the crop, intelligent agriculture technology is used, implementing the control system of variables and records in real time, the conditions and requirements of controlled atmosphere and the vital needs in the support of the plant. Once the fructification phase has started, the system provides the potential nutrients according to the established program, to achieve the objective in the product.